2020
DOI: 10.1007/s10570-020-03535-6
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-dependence of the hydroxyl accessibility in Norway spruce wood

Abstract: This study aimed at a better understanding of the wood-water interaction, in particular the role of the hydroxyl accessibility during the humidity-dependent change in moisture content. Thin sections (80 µm) of never-dried Norway spruce sapwood that contained early- and latewood were used for the experiments. Sorption isotherm measurements confirmed the humidity-dependent moisture content changes and the effect of the first drying of the wood sections. Changes in hydroxyl accessibility were then determined by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
(74 reference statements)
5
9
0
1
Order By: Relevance
“…Similar findings were reported by Salmén and Stevanic (2018), who showed that a reduction in water retention and an increase in cellulose microfibril size due to drying were not accompanied by changes in relative OH accessibility in never-dried pulp fibres. Overall, the current observations were well in line with a number of recent studies, which showed that the accessible OH groups as sorption sites are not the main factor that determines the amount of absorbed water in native wood (Altgen and Rautkari 2021), thermally treated wood (Willems et al 2020;Lillqvist et al 2019) or chemically modified wood (Thybring et al 2020).…”
Section: Moisture Content and Hydroxyl Accessibilitysupporting
confidence: 92%
See 4 more Smart Citations
“…Similar findings were reported by Salmén and Stevanic (2018), who showed that a reduction in water retention and an increase in cellulose microfibril size due to drying were not accompanied by changes in relative OH accessibility in never-dried pulp fibres. Overall, the current observations were well in line with a number of recent studies, which showed that the accessible OH groups as sorption sites are not the main factor that determines the amount of absorbed water in native wood (Altgen and Rautkari 2021), thermally treated wood (Willems et al 2020;Lillqvist et al 2019) or chemically modified wood (Thybring et al 2020).…”
Section: Moisture Content and Hydroxyl Accessibilitysupporting
confidence: 92%
“…In line with previous studies on hydrothermal treatments of wood (Altgen et al 2016(Altgen et al , 2018bKymäläinen et al 2018;Altgen and Rautkari 2021), the sample MC decreased with increasing treatment intensity, i.e. the HWE treatment time (Fig.…”
Section: Moisture Content and Hydroxyl Accessibilitysupporting
confidence: 91%
See 3 more Smart Citations